In Carpal Tunnel Syndrome, Sensory Nerve Conduction Velocities Are Worst in the Middle Finger Than in the Index Finger - Tada, Kaoru; Murai, Atsuro; Nakamura, Yuta; Nakade, Yusuke; Tsuchiya, Hiroyuki (Frontiers in Neurology, 2022)
Although the index finger is generally used for sensory nerve conduction study in cases of carpal tunnel syndrome, there are reports that the middle finger should be used. The purpose of this study was to compare the results of sensory nerve conduction studies of the index finger and middle finger in patients with carpal tunnel syndrome. Among the 120 hands of 93 patients who were diagnosed with carpal tunnel syndrome and underwent carpal tunnel release surgery at our hospital, 54 hands of 48 patients who showed waveforms in sensory nerve conduction studies both index and middle fingers were included. 6 hands of 6 patients who showed no waveform in the index or middle finger, and 60 hands of 39 patients who showed no waveform in both index and middle finger were excluded. The subjects were 14 males and 34 females, and their ages were 66.2 years. The preoperative sensory nerve action potential (µV) and sensory nerve conduction velocity (m/sec) of the index and middle fingers were tested using Wilcoxon's signed rank test. Spearman's rank correlation coefficient was also calculated for the results of the index and middle fingers. Sensory nerve action potentials were 2.0 in the index finger and 1.8 in the middle finger, with significantly lower in the middle finger. Sensory nerve conduction velocity was 30.1 in the index finger and 27.2 in the middle finger, with significantly lower in the middle finger. The correlation coefficients of sensory nerve action potentials and conduction velocities between the index finger and middle finger were 0.82 and 0.96, respectively, both of which showed a significant correlation. The results of the sensory nerve conduction studies of the middle finger were significantly worse than those of the index finger in cases of carpal tunnel syndrome. In addition, there was a strong correlation between the results of the index finger and the middle finger. The results of this study suggest that the middle finger should be examined in sensory nerve conduction studies for the detection of nerve damage associated with carpal tunnel syndrome.